Response Of Growth And Production Of Shallot To The Genus Of Mycorrhiza And Npk Fertilizer - Muhammad, Muhammad; Fajri, Ahmad Dio; Parwi, Parwi; Parwito, Parwito; Susilo, Edi (SINTA Journal (Science, Technology, and Agricultural), 2023)
Mycorrhizal biofertilizer is a biotechnology agent and bio protector that is environmentally friendly and supports the concept of sustainable agriculture. The purpose of this study was to determine the effect of growth and production of shallots on the application of the genus Mycorrhizae and N,P,K fertilizers. This study used a completely randomized design method with two factors: The first factor was the application of the mycorrhizal genera Glomus (M1), Gigaspora (M2), Acaulospora (M3), and the Mycorrhizal Consortium (M4); and the second factor is 0-gram NPK fertilizer (NPK0), 25-gram NPK fertilizer (NPK25), 50-gram NPK fertilizer (NPK50), 75-gram NPK fertilizer (NPK75). The results of the identification of Glomus spore form is obovoid, the spore wall is more than one layer, yellow in color. Gigaspora spore form is globose, spore walls do not have an inner wall, and the spore is yellowish cream in color. Acaulospora spore is elliptic, has 2 spore walls, spores are yellow. The results of mycorrhizal responses and doses of NPK fertilizer on the growth and production of shallots were not significantly different according to the analysis of variance in all observation parameters, but some treatments consistently produced the highest results among other treatments. The highest treatment was M1.NPK50 produced an average number of shallots of 50 pieces, the number of shallot bulbs averaged 13.4 and the diameter of shallot bulbs averaged 4.9.